Helicobacter pylori sabA, hopQ and hom genotypes as potential genetic biomarkers for gastric mucosal inflammation - Hunowu, Ramdan; Fauzia, Kartika A.; Alfaray, Ricky I.; Dewi, Selva R.; Juniastuti, Juniastuti; Yamaoka, Yoshio; Miftahussurur, Muhammad (Narra Sains Indonesia, 2025)
Helicobacter pylori infection drives heterogeneous gastric pathologies, yet genotype-phenotype correlations in diverse populations remain underexplored. The aim of this cross-sectional study was to investigate the associations between H. pylori virulence genotypes (sabA, hopQ, hom family) and histopathological severity in gastric mucosa among 113 Indonesian dyspepsia patients (mean age: 49.6 years; male predominance: 64.6%). Whole-genome sequencing characterized virulence genotypes, while histopathological grading system using the Updated Sydney System assessed inflammation, atrophy, and bacterial density in the antral and corporal gastric regions. Phylogenetic analysis elucidated strain relatedness. Key genotype frequencies included sabA